Evaluación de la percepción climática en fincas citricultoras del cantón pichincha bajo un enfoque de adaptación basada en ecosistemas AbE - Del Valle Basurto, Carmen Melina (2024)
The research aimed to evaluate climate perception in citrus farms in San Sebastián, Pichincha canton, under an EbA approach. Information was gathered through a survey technique with sociodemographic, productive, and climate perception data from the study area. To determine the response and recovery capacity of farmers to climate change, the traffic light scale was used with 9 indicators, and vulnerability was measured with 6 indicators. Finally, the resilience level of the farms was assessed through 28 biophysical and socioeconomic indicators, using a valuation range from 0 (none) to 1 (excellent), and EbA strategies focused on citrus farming were established. The results showed that farmers possess knowledge about climate change and its effects on citrus production. However, there is evidence of a lack of response and recovery capacity, as 60% of the studied farms showed a "medium" level with a yellow color according to the valuation scale. It was determined that 50% of the farms have "medium vulnerability." Meanwhile, the resilience level varies among the farms: 1, 2, 4, 5, and 9 "very high resilience"; 3, 6, and 7 "low resilience"; 8 and 10 "medium resilience." It is concluded that establishing strategies under an EbA approach helps improve the response capacity and resilience of citrus farm farmers to the effects of climate change.